(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
We have discussed a broad variety of topics, including phase service queueing models, in our conversations. In the realm of queueing theory, a number of models have been developed that include the concept of phased service. Several different types of daily and industrial situations have been tried to see whether these phase service queueing approaches are effective at alleviating congestion. This paper attempts to review the research done on phase service queues by the most eminent academics, as well as the study’s relevance in a range of real-world queueing settings. Researchers’ strategies for dealing with phase service queueing models have also been made public by a number of them. With the use of modelling and scientific techniques, we were able to organise all of the pertinent information. The primary audience for this work consists of system analysts, managers, and industry experts who are interested in applying queueing theory to analyse congestion situations when phase-type services are prevalent and who are interested in applying queueing theory to analyse congestion situations when phase-type services are prevalent.